Government Employee Assessment to Support Public Performance Organization Learned from Riau Island Province - Nolla Puspita Dewi; Indrayani Indrayani; Chabullah Wibisono; Angelina Eleonora Rumengan (Cogent Business & Management, 2024)
The government management system is expected to focus on increasing accountability and at the same time improving the performance of outcome-oriented employees. This study aims to examine and analyze the relationship between the performance of integrity, competence, work environment, intrinsic motivation, and organizational commitment in Government Employee of the Riau Islands Province. This research uses Structural Equation Modeling (SEM) Lisrel 8.70 method in data processing. Survey research uses a questionnaire with a population of 515 samples of 225 (slovin formula). The analysis results show that organizational commitment significantly affects performance, followed by integrity, intrinsic motivation, and competence. Intrinsic motivation can mediate work environment and integrity in performance. Therefore, this study shows the factors that have the most effect on government employees' performance and how these factors can be improved to enhance their performance. However, this study has some limitations, such as generalizing the study's results only to Riau Islands Province and not considering other factors, such as organizational culture and external factors. Therefore, future research can involve a more comprehensive sample and consider other factors that affect the performance of government employees. This research provides valuable information for government and public organizations to develop effective employee performance appraisal strategies and improve overall government employee performance.
Keywords: 650; government employee; assessment; Public Performance Organization